DINAMIKA MOTIVASI KERJA PEGAWAI NEGERI SIPIL WANITA TERKAIT STATUS PERNIKAHAN - I P Sonny Mandala Putra; Yohanes Kartika Herdiyanto (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
The phenomenon of working woman is a common thing in life. Data from Central Statistic Department (BPS) stated that around 47.91 of the productive worker are women population and relatively balanced with men population which describes women could have the same opportunity with men for work. Civil servant is one of the most occupations that intensively hiring for worker especially in Bali (BPS, 2012). It is an interesting phenomenon to know the working motivation of civil servant whom hired a lot of worker related into marriage status. This explanation were supported by the preliminary finding on preliminary study that shows there are differences working motivation between civil servant who were married and unmarried.This study used qualitative research method with case study design. Collecting data use interview and observation. Respondents in this study were four civil servant women which consist of two unmarried and married respondents. To strengthen data, interview were also conducted with significant others of respondents.The results showed that working motivation on civil servant women can be drawn from: (1) the reason for choosing job is both internal and external; (2) working purpose is goal of independence, self-exploration, economics, and recognition or existence; and (3) income issues for their future. Difference in the use of income is affected by marriage system related to patrilineal system of inheritance law regarding women status in law. Based on three findings and analysis of cultural studies, found that between married and unmarried respondents have differences related needs of motivation. Keywords: work motivation, female civil servants, marital status